ABP-B9, a new strain of Pseudomonas seleniipraecipitans with biostimulant activity - Bernal-Vicente, Agustina; Sánchez-Pujante, Pedro Joaquín; Diaz-Vivancos, Pedro; Donaire, Livia; Aranda, Miguel A.; Hernando, Yolanda (Frontiers in Plant Science, 2025)
IntroductionMicroorganisms are emerging as key agents in sustainable agriculture due to their ability to enhance crop productivity while reducing environmental impact. Among them, Pseudomonas spp. are well known for promoting plant growth through mechanisms such as phytohormone production and improved nutrient availability. This study describes the characterization of the strain ABP-B9, isolated from the rhizosphere of commercial lettuce crops.Materials and methodsABP-B9 was evaluated under both field and controlled conditions to assess its plant growth-promoting effects. Parameters such as root development, photosynthetic efficiency, flavonoid content, nitrogen status, and the production of indole-3-acetic acid (IAA) and siderophores were measured. Whole-genome sequencing and phylogenetic analysis were also performed.ResultsField trials showed that ABP-B9 enhanced crop yield in lettuce, spinach, and celery, improving root development, photosynthetic efficiency, flavonoid levels, and nitrogen status. The production of IAA and siderophores was confirmed in vitro. Plant responses were observed as early as five days after application. Genomic analysis revealed that ABP-B9 belongs to the Pseudomonas genus and is closely related to P. seleniipraecipitans. Its genome (4,602,210 bp; 61.46% GC content) includes 4,247 protein-coding genes, 12 rRNAs, and 66 tRNAs.DiscussionABP-B9 is a novel, non-pathogenic Pseudomonas strain with clear biostimulant activity. Its ability to enhance plant growth and increase crop yield, combined with its safety profile, supports its potential use in sustainable agriculture. Future studies should explore its application across different crops and environmental conditions.